Methods for NMR-spectrum prediction - Robien, Wolfgang (Henry Stewart Talks, 2011)
HOSE-Code technology prediction, Neural network (NN) technology, Comparison HOSE-NN prediction, Combined application of two techniques, Prediction with or without stereochemistry, Prediction quality using statistical techniques, Using spectrum prediction, Prediction using increments, Arosim program, The quality of the literature, Prediction vs. literature, Impact Factor and quality of C-NMR data, Robot-Referee as tool for improvement, A matching map, Using spectroscopic databases